Evaluating the Mediating Role of Job Satisfaction on Employee Performance Improvement - Haryadi, Didit; Qorin, Ihya Ashabul; Diantoro, Eman; Karliena, Yayuk; Yulia, Lika; Fahmi, Irma (Journal of Business and Economics Research (JBE), 2025)
Growing public involvement in government decision-making processes requires employees to have strong interpersonal and communication skills. This study aims to examine the relationship between workplace culture, employee commitment, job satisfaction, and employee performance in the operational context of the Cilegon City Office of the Ministry of Religious Affairs. This study used quantitative methodology. The study population consisted of 536 employees, consisting of 396 State Civil Apparatus employees and 140 non-State Civil Apparatus employees. The researchers used proportional stratified random sampling, basing the sample size on the number of variable indicators: 20 indicators multiplied by 8, resulting in 160 respondents. The findings of this study reveal that organizational culture has an impact on employee performance with a t-statistic value of 5.530 > 1.96 and a p-value of 0.000 < 0.05, while organizational commitment does not with a t-statistic value of 1.632 < 1.96 with a p-value of .103 > 0.05. In addition, organizational culture on job satisfaction has a t-statistic value of 3.435 > 1.96 t-table significance 0.000 < 0.05 and organizational commitment affects employee job satisfaction with a t-statistic value of 4.173 > 1.96 t-table significance value 0.000 < 0.05. The third hypothesis confirms that job satisfaction affects employee performance with a t-statistic value of 4.704 > 1.96 t-table with a significance value of 0.000 < 0.05. Finally, job satisfaction functions as a mediating variable, increasing the influence of organizational culture and organizational commitment on employee performance with partial mediation. By using a quantitative approach and rigorous data analysis, this study aims to provide a comprehensive insight into the factors that shape employee performance and provide practical implications for organizational management to improve work effectiveness and efficiency.